Special Education Major or Attitudes to Predict Teachers' Self-Efficacy for Teaching in Inclusive Education - Alnahdi, Ghaleb H.; Schwab, Susanne (Frontiers in Psychology, 2021)
This study aimed to determine the predictors for Saudi Arabian teachers’ self-efficacy to work in inclusive education . Five independent variables were tested in this study: attitudes towards inclusive education, participants’ educational major, having relative with disability, working with students with disability and gender. Further, as well as to examine the predictors of teachers’ attitudes towards inclusive education were examined. The sample was 185 elementary-school teachers in Saudi Arabia. The Arabic version of the Teacher Efficacy for Inclusive Practices scale was used to measure self-efficacy. To assess attitudes towards inclusion an Arabic version of the , and a Sentiments, Attitudes, and Concerns about Inclusive Education Revised subscale was used to measure attitudes towards inclusion. Results showed teacher attitude towards inclusion was the best predictor ofare strongly linked with teachers’ self-efficacy to work in inclusive classrooms. Further , and participants with a relative with a disability showed more positive attitudes for inclusive education. Levels of self-efficacy were unaffected by gender, having a special education degree, or having a relative with a disability. In sum, this study highlighted the importance of teachers’ attitudes towards inclusive education as a main predictor of teachers’ self-efficacy.